2020
DOI: 10.3390/cells9102227
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Hybrid Adeno-Associated Viral Vector Transposon System to Deliver the Insulin Gene to Diabetic NOD Mice

Abstract: Previously, we used a lentiviral vector to deliver furin-cleavable human insulin (INS-FUR) to the livers in several animal models of diabetes using intervallic infusion in full flow occlusion (FFO), with resultant reversal of diabetes, restoration of glucose tolerance and pancreatic transdifferentiation (PT), due to the expression of beta (β)-cell transcription factors (β-TFs). The present study aimed to determine whether we could similarly reverse diabetes in the non-obese diabetic (NOD) mouse using an adeno-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…By combining the entry properties of viral vectors and the integrative properties of DNA transposons, hybrid viral-transposon vectors ( Figure 3 ) can this way maintain stable long-term expression while enabling the reduction of the viral load. Recombinant adeno-associated viral vectors (rAAVs) have been successfully used with the PB [ 142 , 143 , 144 , 145 , 146 ] and SB [ 147 ] transposon systems to enable integration of the DNA material while taking advantage of AAV tropism towards specific tissues for in vivo delivery. PB [ 146 , 148 ] and SB [ 147 , 149 , 150 , 151 , 152 , 153 , 154 ] have also been used with adenoviral (AdV) vectors, baculovirus expression vectors (BEVs), and herpes simplex virus type-1 (HSV) vectors to benefit from their large payload capacity (up to 36 kb, 50 kb, and 130 kb, respectively) and their respective intrinsic properties, namely AdV’s broad tropism, BEV’s low cytotoxicity, and HSV’s preference for the central nervous system.…”
Section: Vectors For Enhanced Delivery Of Transposon Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining the entry properties of viral vectors and the integrative properties of DNA transposons, hybrid viral-transposon vectors ( Figure 3 ) can this way maintain stable long-term expression while enabling the reduction of the viral load. Recombinant adeno-associated viral vectors (rAAVs) have been successfully used with the PB [ 142 , 143 , 144 , 145 , 146 ] and SB [ 147 ] transposon systems to enable integration of the DNA material while taking advantage of AAV tropism towards specific tissues for in vivo delivery. PB [ 146 , 148 ] and SB [ 147 , 149 , 150 , 151 , 152 , 153 , 154 ] have also been used with adenoviral (AdV) vectors, baculovirus expression vectors (BEVs), and herpes simplex virus type-1 (HSV) vectors to benefit from their large payload capacity (up to 36 kb, 50 kb, and 130 kb, respectively) and their respective intrinsic properties, namely AdV’s broad tropism, BEV’s low cytotoxicity, and HSV’s preference for the central nervous system.…”
Section: Vectors For Enhanced Delivery Of Transposon Systemsmentioning
confidence: 99%
“…Various groups have combined AAV vectors, lacking the ability to integrate their cargo, with the PB transposon system. Using this strategy, diabetes type I [ 142 ], urea cycle defects [ 143 ], cystic fibrosis [ 145 ], and progressive familial intrahepatic cholestasis type 3 [ 144 ] were corrected in pig and mouse models. Other studies on cancer therapies have reported a reduction of tumor growth in mice and increased lifespan with hybrid SB-baculovirus vectors [ 150 , 151 , 152 ].…”
Section: Preclinical Applicationsmentioning
confidence: 99%
“… 97 , 98 The AAV-PB system has also been used successfully for insulin gene delivery in a mouse model of diabetes, resulting in normoglycaemia and glucose tolerance. 99 …”
Section: Viral Vectorsmentioning
confidence: 99%
“…However, we and others have shown that a similar glucose tolerance profile was also observed in mice treated with insulin under a constitutive promoter. 79,80 Furthermore, hypoglycemia remained a risk even with glucose-responsive promoters. 79,81 The main shortcoming of present-day insulin gene therapy strategies remains the absence of insulin secretory granules, unlike that in b cells.…”
Section: Reviewmentioning
confidence: 99%
“…74,[86][87][88] Non-integrative adenovirus can last for at most a few months. 71,77,[89][90][91][92][93] While adeno-associated virus (AAV) and AAV hybrid vectors are more long-lasting, 76,80,81 they prevent re-administration as a top-up strategy due to antibodies formed against the viral vectors. Repeated dosing strategies such as using a different AAV capsid, 94 neutralization of antibodies, 95 or immune suppression 96 are being studied.…”
Section: Reviewmentioning
confidence: 99%